2021
DOI: 10.3390/cancers13184623
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on the Role of Microbiome for Colorectal Cancer Treatment

Abstract: In healthy hosts, trillions of microbes colonise the gut and oral cavity in a well-balanced state, maintaining a mutually beneficial relationship. Loss of this balance, termed dysbiosis, is strongly implicated in the pathogenesis of colorectal cancer (CRC). However, the roles of microbiota and dysbiosis in CRC treatment remain poorly understood. Recent studies suggest that the gut microbiota has the ability to affect the host response to chemotherapeutic agents by enhancing drug efficacy, promoting chemoresist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 126 publications
0
7
0
Order By: Relevance
“…Gut microbes aid towards the maintenance of intestinal homeostasis, prevent pathogen colonization and release key nutrients and energy from the diet. Apart from the benefits, it has been demonstrated in previous studies that gut microbes may play a role similar to tumor suppressor or oncogenes ( 20 , 21 ). The microbiome communicates with host via direct and indirect factors, such as metabolites, proteins and toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbes aid towards the maintenance of intestinal homeostasis, prevent pathogen colonization and release key nutrients and energy from the diet. Apart from the benefits, it has been demonstrated in previous studies that gut microbes may play a role similar to tumor suppressor or oncogenes ( 20 , 21 ). The microbiome communicates with host via direct and indirect factors, such as metabolites, proteins and toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a murine model of intestinal mucositis in the context of the antineoplastic agent cisplatin, the 16S rRNA sequencing analysis of fecal DNA indicated that cisplatin induces dysbiosis with a significant increase in Bacteroidaceae and Erysipelotrichaceae families and Bacteroides uniformis , with a decrease in Ruminococcus gnavus [ 120 ].…”
Section: The Interplay Between Microbiota and Cancer Treatmentmentioning
confidence: 99%
“…Microbiota can affect the response to chemotherapy. It has been observed that some bacteria metabolize and reduce the effects of chemotherapy at the tumor site (239). Besides, microbiota are chief players in regulating inflammatory responses in GI, through which they can influence the response of CRC patients to immunotherapy (240)(241)(242).…”
Section: Role Of the Microbiome In Personalized Immunotherapymentioning
confidence: 99%